2019
DOI: 10.3390/min9020121
|View full text |Cite
|
Sign up to set email alerts
|

FTIR-Based Crystallinity Assessment of Aragonite–Calcite Mixtures in Archaeological Lime Binders Altered by Diagenesis

Abstract: Lime plaster and mortar are pyrotechnological materials that have been employed in constructions since prehistoric times. They may nucleate as calcite and/or aragonite under different environmental settings. In nature, aragonite and calcite form through biogenic and geogenic processes that lead to different degrees of atomic order. The latter is a result of defects in the crystal lattice, which affect the properties of crystals, including their interaction with infrared light. Using Fourier transform infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 56 publications
4
28
0
1
Order By: Relevance
“…These characteristic peaks of aragonite polymorph have been reported by several researchers [24]. CO 3 2− ions remain inactive in the infrared region and that the band at 1081 cm −1 cannot be seen in the pure calcite phase of calcium carbonate has already been verified in the previous literature [27] [28]. Apart from stretching vibrations, out-of-plane and inplane bending of C-O bond resembling absorption band at 873 and 712 cm −1 are attributed to calcite phases in the sample [28].…”
Section: Handsheet Preparation and Characterizationsupporting
confidence: 74%
See 2 more Smart Citations
“…These characteristic peaks of aragonite polymorph have been reported by several researchers [24]. CO 3 2− ions remain inactive in the infrared region and that the band at 1081 cm −1 cannot be seen in the pure calcite phase of calcium carbonate has already been verified in the previous literature [27] [28]. Apart from stretching vibrations, out-of-plane and inplane bending of C-O bond resembling absorption band at 873 and 712 cm −1 are attributed to calcite phases in the sample [28].…”
Section: Handsheet Preparation and Characterizationsupporting
confidence: 74%
“…CO 3 2− ions remain inactive in the infrared region and that the band at 1081 cm −1 cannot be seen in the pure calcite phase of calcium carbonate has already been verified in the previous literature [27] [28]. Apart from stretching vibrations, out-of-plane and inplane bending of C-O bond resembling absorption band at 873 and 712 cm −1 are attributed to calcite phases in the sample [28]. The IR spectra of industrially manufactured PCC used in this study have similar absorption bands as per the published literature data revealed from Fig.…”
Section: Handsheet Preparation and Characterizationsupporting
confidence: 61%
See 1 more Smart Citation
“…Similarly, geogenic aragonite exhibits a different grinding curve compared with biogenic aragonite and aragonite precipitated from boiling water (Suzuki, Dauphin, Addadi, & Weiner, 2011). Toffolo, Regev, Dubernet, Lefrais, and Boaretto (2019) extended the method to pyrogenic aragonite and developed a procedure based on FTIR and XRD to determine degrees of atomic order in calcite–aragonite mixtures (Figure 3). Powdered samples may be analyzed also in attenuated total reflectance (ATR) mode (e.g., Loftus, Rogers, & Lee‐Thorp, 2015; Villagran, Strauss, Miller, Ligouis, & Oliveira, 2017).…”
Section: Basic Properties Of Aragonitementioning
confidence: 99%
“…Crystals may show different degrees of atomic order in mollusks, as shown by FTIR grinding curves of nacre, myostracum, ligament, and crossed‐lamellar aragonite (Suzuki et al, 2011). Figure 3 shows the grinding curve of a powdered Glycymeris insubrica (bittersweet clam) shell compared with other aragonite reference standards (Toffolo, Regev, et al, 2019). Stony corals (phylum Cnidaria, class Anthozoa, order Scleractinia) mineralize aragonite exoskeletons (Lowenstam & Weiner, 1989).…”
Section: Basic Properties Of Aragonitementioning
confidence: 99%